Early deictic but not other gestures predict later vocabulary in both typical development and autism. (August 2016) - Özçalışkan, Şeyda; Adamson, Lauren B; Dimitrova, Nevena
Research with typically developing children suggests a strong positive relation between early gesture use and subsequent vocabulary development. In this study, we ask whether gesture production plays a similar role for children with autism spectrum disorder. We observed 23 18-month-old typically developing children and 23 30-month-old children with autism spectrum disorder interact with their caregivers (Communication Play Protocol) and coded types of gestures children produced ( deictic, give, conventional, and iconic ) in two communicative contexts (commenting and requesting). One year later, we assessed children's expressive vocabulary, using Expressive Vocabulary Test. Children with autism spectrum disorder showed significant deficits in gesture production, particularly in deictic gestures (i.e. gestures that indicate objects by pointing at them or by holding them up). Importantly, deictic gestures—but not other gestures—predicted children's vocabulary 1 year later regardless of communicative context, a pattern also found in typical development. We conclude that the production of deictic gestures serves as a stepping-stone for vocabulary development.